Dehydrogenation of Cyclohexanol to Cyclohexanone Over Nitrogen-doped Graphene supported Cu catalyst - Alyaa. K. Mageed; Dayang A. B. Radiah; A. Salmiaton; Shamsul Izhar; Musab Abdul Razak; Bamidele Victor Ayodele (Bulletin of Chemical Reaction Engineering & Catalysis, 2020)
In this study, the dehydrogenation of cyclohexanol to cyclohexanone over nitrogen-doped reduced graphene oxide (N-rGO) Cu catalyst has been reported. The N-rGO support was synthesized by chemical reduction of graphite oxide (GO). The synthesized N-rGO was used as a support to prepare the Cu/N-rGO catalyst via an incipient wet impregnation method. The as-prepared support and the Cu/N-rGO catalyst were characterized by FESEM, EDX, XRD, TEM, TGA, and Raman spectroscopy. The various characterization analysis revealed the suitability of the Cu/N-rGO as a heterogeneous catalyst that can be employed for the dehydrogenation of cyclohexanol to cyclohexanone. The catalytic activity of the Cu/N-rGO catalyst was tested in non-oxidative dehydrogenation of cyclohexanol to cyclohexanone using a stainless-steel fixed bed reactor. The effects of temperature, reactant flow rate, and time-on-stream on the activity of the Cu/N-rGO catalyst were examined. The Cu/N-rGO nanosheets show excellent catalytic activity and selectivity to cyclohexanone. The formation of stable Cu nanoparticles on N-rGO support interaction and segregation of Cu were crucial factors for the catalytic activity. The highest cyclohexanol conversion and selectivity of 93.3% and 82.7%, respectively, were obtained at a reaction temperature of 270 °C and cyclohexanol feed rate of 0.1 ml/min. Copyright © 2020 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).